DARI ARCA KE ARJA: ADAPTASI PANJI DALAM PERTUNJUKAN ARJA DI BALI - Koes Yuliadi (BRIN, 2013)
Panji stories that were spread throughout Indonesia and Southeast Asia were not only known as old literature. Panji stories were also sculpted as the reliefs on temples in East Java. The existence of the text shows the historical facts that form the basis for the emergence of the Panji stories. Panji figure could be a manifestation of the life of kings in the past. The presence of papyrus, relief, and also stage performance that tell the story of Panji showed that there is a correlation among literature, relief, and performance, in the realm of art creation. Are Panji stories stay preserved as part of the development of art in Indonesia? Arja performances in Bali could describe how Panji stories can still be traced. Arja's performance used Panji stories as a source. Now Arja is existence can still be seen through its variety of plays. However, this does not make the panji story disappear in the Arja's performance. This issue will be addressed as a consequence of the adaptation of the revolving art. Not only in the present, but in the past a pattern of adaptation that can transpose works from different disciplines has already emerged. Panji stories can be known through papyrus, relief, and performances. Today it is still going without being recognized.